2017
DOI: 10.1186/s40201-017-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

An optimized SPE-LC-MS/MS method for antibiotics residue analysis in ground, surface and treated water samples by response surface methodology- central composite design

Abstract: BackgroundAntibiotic residues are being constantly identified in environmental waters at low concentration. Growing concern has been expressed over the adverse environmental and human health effects even at low concentration. Hence, it is crucial to develop a multi-residues analytical method for antibiotics to generate a considerable dataset which are necessary in the assessment of aquatic toxicity of environmental waters for aquatic organisms and human health. This work aimed to develop a reliable and sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 61 publications
(107 reference statements)
1
33
0
1
Order By: Relevance
“…For the third process, prior to use of Strata-X or HLB cartridges, an addition of 0.3% Na 2 EDTA reduced the matrix effects and slightly enhanced the recovery yields. Indeed, the third procedure offered high recovery yields for all the antibiotics (89.3-107.4%), whose results were comparable to previous works [19][20][21][23][24][25][27][28][29][30]70,72,74,75], but it required a long sample preparation time of 40 min/sample. Briefly, higher cost and longer sample preparation time were the main drawbacks of the second and the third procedures, compared to the first process, which had a short preparation time of 10 min/sample and was 60% cheaper (Figures S22-S25 in SM).…”
Section: Optimization Of Sample Preparationsupporting
confidence: 84%
See 1 more Smart Citation
“…For the third process, prior to use of Strata-X or HLB cartridges, an addition of 0.3% Na 2 EDTA reduced the matrix effects and slightly enhanced the recovery yields. Indeed, the third procedure offered high recovery yields for all the antibiotics (89.3-107.4%), whose results were comparable to previous works [19][20][21][23][24][25][27][28][29][30]70,72,74,75], but it required a long sample preparation time of 40 min/sample. Briefly, higher cost and longer sample preparation time were the main drawbacks of the second and the third procedures, compared to the first process, which had a short preparation time of 10 min/sample and was 60% cheaper (Figures S22-S25 in SM).…”
Section: Optimization Of Sample Preparationsupporting
confidence: 84%
“…The separation was achieved by using a ternary gradient mobile phase consisting of ACN (A), MeOH (B), and water with 0.1% formic acid (C). The total required time for the chromatographic analysis was 20 min, which was comparable or shorter than the time spent of 20-40 min in [27,31,32]. The optimal conditions are listed in Table 2 and presented in Figure 1.…”
Section: Chromatographic Optimizationmentioning
confidence: 91%
“…According to EPA 1694, the filtration of the samples is necessary in order to remove suspension solids. Two filtration steps were carried out prior to analysis using glass fiber filters (1.6 µm, supplied by GVS) for the first filtration stage and nylon filters (0.45 µm, supplied by GVS) for the second stage, as suggested in other research works [33][34][35].…”
Section: Site Description and Sample Collectionmentioning
confidence: 99%
“…The simultaneous determination of pharmaceuticals in wastewater is a challenging task due to the variation in their physicochemical properties, their low concentrations, and complexity of the environmental matrices [19,20,21,22,23,24,25]. Based on the literature surveys regarding the most commonly prescribed medications in the Emirate of Sharjah, it was found that the percentage of prescribing antibiotics to treat different types of infections was 45% [26].…”
Section: Introductionmentioning
confidence: 99%